Girl online going solo - Sugg, Zoe 1990- (New York Keywords Press, 2016)
Sixteen-year-old blogger Penny takes the advice of her online commenters in the wake of her break up with Noah, concentrating on her best friend Elliot who needs her now more than ever, working on her photography project for her internship, and making new friends, including a student actress with stage fright and a Scottish photographer who might drive away the ghost of Noah
Originally published in Great Britain by Penguin Books in 2016
Sequel to: Girl online : on tour
1
Keywords: Blogs -- Fiction; Dating (Social customs) -- Fiction; Photography -- Fiction